Effects of estrogen deprivation on expression of aquaporins in rat vagina. Issue 8 (August 2015) - Zhu, Jiyin; Xia, Jiyi; Jiang, Jun; Jiang, Rui; He, Yanzheng; Lin, Haocheng
Abstract: Objective: This study aims to investigate the expression of aquaporin (AQP) 0, AQP3, AQP5, AQP6, AQP10, AQP11, and AQP12 in the vaginal tissue of ovariectomized rats. Methods: Eight-week-old female Sprague-Dawley rats (n = 18) were randomly divided into three groups: control group (n = 6), ovariectomy group (n = 6), and ovariectomy/estrogen therapy group (n = 6). After 4 weeks, vaginal lubrication level and expression of AQP0, AQP3, AQP5, AQP6, AQP10, AQP11, and AQP12 in vaginal tissue were examined. Results: Serum estrogen level was significantly lower in the ovariectomy group than in the control and ovariectomy/estrogen therapy groups ( P < 0.05). Vaginal lubrication was significantly lower in the ovariectomy group (mean [SD], 1.62 [0.30]) than in the control group (mean [SD], 2.37 [0.70]) and ovariectomy/estrogen therapy group (mean [SD], 2.38 [0.73]; P < 0.05). Protein expression of AQP0, AQP3, AQP5, AQP6, AQP10, AQP11, and AQP12 was significantly lower in the ovariectomy group than in the control and ovariectomy/estrogen therapy groups ( P < 0.05). Conclusions: Decreased vaginal lubrication in ovariectomized rats after electrostimulation may be partly caused by decreased AQPs in vaginal tissue.